IMPLEMENTASI SATUAN PENDIDIKAN AMAN BENCANA DI SD MUHAMMADIYAH SAPEN - septikasari, zela; Perwitasari , Ningrum; Anggraini , Deri; Bahtiar , Riski; Kurniawan , Ficky Adi; Handaka , Irvan Budhi (LPPM Universitas PGRI Argopuro Jember, 2026)
Efforts to improve disaster preparedness have not been fully implemented at SD Muhammadiyah Sapen. In 2022, a joint disaster awareness campaign was conducted, but it only involved 30 teachers and 3 classes. Disaster preparedness at SD Muhammadiyah Sapen is identified as still very inadequate, given the large number of school staff who lack knowledge and skills regarding disasters, the absence of sustained integration of disaster education, the lack of regular simulations, and insufficient disaster-related facilities and infrastructure. The history of disasters and their impacts at the school highlight the importance of implementing the Disaster-Resilient Educational Unit (SPAB). SPAB serves as an effective tool for providing information, knowledge, and skills to school community members regarding disaster response. Implementing SPAB can enhance the preparedness of school community members, strengthen the school’s capacity, and thereby reduce risks during disasters. This aligns with UPY’s roadmap for community service, specifically the development of disaster-resilient regions. The activities will be conducted in accordance with the three pillars of SPAB: safe school facilities, disaster management in schools, and education on disaster prevention and risk reduction. Implementation methods include lectures, group discussions, practical exercises, and simulations. Activity outcomes include disaster risk assessments, school action plans, early warning systems, evacuation plans, the formation of school disaster response teams, standard operating procedures for disaster emergencies, table top exercise (TTX), and disaster simulations. The evaluation of the SPAB programme demonstrated an improvement in the knowledge and skills of school communities in dealing with disasters. The Community Service Programme (PKM) of the Research and Community Service Institute (LPPM) at Universitas PGRI Yogyakarta has proven that a collaborative and school-based approach is effective in enhancing schools' resilience to disasters.